Natural language processing and machine learning in the categorization of scientific papers: a study around ?cultural heritage? - Jesus, Ananda Fernanda de [UNESP]; Triques, Maria Ligia; Segundo, Jose Eduardo Santarem [UNESP]; Albuquerque, Ana Cristina de (Univ Brasilia, Dept Ciencia Informacao, 2023)
Aims to verify the potential of applying Natural Language Processing (NLP) and Machine Learning (ML) techniques in the thematic categorization of scientific articles on the theme cultural heritage from two situations in which categories are established a priori and later. Applied research is developed, with quantitative and qualitative results, where the first corpus consisting of scientific articles in Portuguese, on a thematic basis of Information Science, manually selected and categorized; and the second corpus, composed of scientific articles in English retrieved from the Web of Science, automatically categorized by search strategies and application of Booleans. Both were submitted to two categorization test procedures (supervised and unsupervised algorithm). The results show that in both, the participation of the researcher is essential in defining the representativeness of the chosen sample, and this has an impact on the precision and accuracy of the applied algorithms. The importance of detailing and rigor in the pre-processing of data and sample size is highlighted, however, it is emphasized that, in the case of this study, only a larger volume of data did not guarantee that the results were representative from the point of view of the domain studied, which warns that there are always multidisciplinary discussions and analyzes that allow verifying and readjusting the sample parameters.
Keywords: Machine learning; Natural language processing; Neural network algorithm; Cultural heritage; Hierarchical clustering algorithm